2014
DOI: 10.1016/j.pmrj.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life, Shoulder Range of Motion, and Spinal Accessory Nerve Status in 5‐Year Survivors of Head and Neck Cancer

Abstract: Objective To determine the association of neck dissection and radiation treatment for head and neck cancer (HNC) with subsequent shoulder range of motion (ROM) and quality of life (QOL) in 5-year survivors. Design Cross-sectional convenience sample Setting Otolaryngology clinics at tertiary care hospital and Veterans Affairs medical center Patients 5-year, disease-free, HNC survivors Methods Demographic and cancer treatment information was collected, including type of neck dissection (none, spinal acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 46 publications
0
29
0
3
Order By: Relevance
“…The negative effect of the extent of neck dissection surgery on shoulder abduction and forward flexion has been described before, and it is partly related to accessory nerve damage [6,23,24]. The only previous cross-sectional study to describe shoulder function at five-year follow-up also reported a negative effect for the extent of ND surgery [10]. The negative effect of bone graft/flap reconstruction is in line with previous studies, which have reported negative effects for extensive reconstructive surgery [6,25].…”
Section: Factors Influencing Shoulder Functionmentioning
confidence: 69%
See 1 more Smart Citation
“…The negative effect of the extent of neck dissection surgery on shoulder abduction and forward flexion has been described before, and it is partly related to accessory nerve damage [6,23,24]. The only previous cross-sectional study to describe shoulder function at five-year follow-up also reported a negative effect for the extent of ND surgery [10]. The negative effect of bone graft/flap reconstruction is in line with previous studies, which have reported negative effects for extensive reconstructive surgery [6,25].…”
Section: Factors Influencing Shoulder Functionmentioning
confidence: 69%
“…Reports on prevalence of shoulder dysfunction exhibit wide variation in how the limitations in function progress over time, and they are often limited to one-year follow-up or a single moment of measurement [9]. One cross-sectional study measuring shoulder range of motion at five-year follow-up reports slightly lower scores for shoulder function, as compared to studies reporting oneyear measurements [10]. There is thus no definitive prognostic information that can be provided to patients during rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Swelling of the face and neck and potential nerve damage may cause further motor, sensory, and functional deficits, such as diminished neck and/or shoulder range of motion (ROM). Significant QoL issues result from this sequelae, causing difficulty managing both basic and advanced activities of daily living (ADLs) [ 9 ]. In partnership with speech language pathologists (SLP) who address potential swallowing and speech limitations, PTs are often consulted to address the negative sequelae of H&N cancer and its treatments.…”
Section: Introductionmentioning
confidence: 99%
“…During head and neck surgery, cranial nerve transection is sometimes anticipated or can occur unintentionally . Cranial nerve injuries can lead to significant morbidity including facial paralysis, dysphagia, shoulder disability, and aspiration . Following complete nerve transection, primary neurorrhaphy with microsuture is the most commonly used repair technique, provided the nerve endings have enough length for primary anastomosis …”
Section: Introductionmentioning
confidence: 99%